Efficacy of posterior pericardiotomy in prevention of atrial fibrillation and pericardial effusion after aortic valve replacement: a randomized controlled trial - V. I. Kaleda; S. Yu. Boldyrev; S. A. Belash; I. I. Yakuba; S. S. Babeshko; I. A. Belan; K. O. Barbuhatti (Патология кровообращения и кардиохирургия, 2017)
Aim. Postoperative atrial fibrillation is one of the most frequent complications in cardiac surgery. The aim of this trial was to evaluate the effectiveness of posterior pericardiotomy in the prevention of postoperative atrial fibrillation and pericardial effusion in patients undergoing isolated primary aortic valve replacement. Methods. The trial was approved by the local ethics committee. It included adult patients under 70 y.o. who had signed the informed consent for participation in the study and who were planned to undergo isolated primary aortic valve replacement. Exclusion criteria were a history of atrial fibrillation, hyperthyroidism, amiodarone intake, severe chronic obstructive pulmonary disease, left ventricle ejection fraction less than 30%, the size of the left atrium exceeding 50 mm, active infective endocarditis, the presence of adhesions in the pericardium and/or left pleural cavity and mini-sternotomy. From October 2013 to April 2015 607 patients in our clinic underwent different aortic valve procedures. 507 patients were excluded from the study because of the inclusion and exclusion criteria. The remaining 100 patients were randomized into two groups: 49 patients underwent posterior pericardiotomy and 51 patients made up the control group. In both groups the frequency of postoperative atrial fibrillation, pericardial effusion greater than 5 mm, surgery-discharge time, as well as posterior-pericardiotomy-related complications were studied. Trial number: ISRCTN11129539. Results. There were no deaths, stroke or cardiac tamponade during the postoperative stay. Neither were there any complications associated with the performance of posterior pericardiotomy. The incidence of atrial fibrillation, pericardial effusion and average duration of the postoperative stay were similar in both groups: 16% in posterior pericardiotomy group vs 14% in the control group (p=0.71), 10% in posterior pericardiotomy group vs 12% in the control group (p=0.80) and 12.4±4.3 days in posterior pericardiotomy group vs 11.9±4.1 days in the control group (p=0.27), respectively. Conclusion. The trial did not confirm the effectiveness of posterior pericardiotomy in preventing postoperative atrial fibrillation and pericardial effusion during the in-hospital period after isolated primary aortic valve replacement in low risk patients. However, further investigations are needed. Received 1 December 2016. Accepted 14 February 2017. Funding: The trial was carried out within the dissertation research and according to the research calendar of Kuban State Medical University. There was no additional funding except for the resources allocated for postgraduate scholarships. Conflict of interest: The authors declare no conflict of interest. Author contributions Conception and study design: V.I. Kaleda, K.O. Barbuhatti. Data collection and analysis: V.I. Kaleda, S.Yu. Boldyrev, S.A. Belash, I.I. Yakuba, S.S. Babeshko, I.A. Belan. Drafting the article: V.I. Kaleda. Critical revision of the article: V.I. Kaleda. Final approval of the version to be published: V.I. Kaleda, S.Yu. Boldyrev, S.A. Belash, I.I. Yakuba, S.S. Babeshko, I.A. Belan, K.O. Barbuhatti. Acknowledgements: The authors would like to express their gratitude to Cand. Sci. (Engineering) V.P. Leonov (“Biometrika”) for assistance in statistical data processing.